FORMULATION AND STABILITY TESTING OF SOLID SOAP CONTAINING A COMBINATION OF PURE HONEY (MEL DEPURATUM) AND RED DRAGON FRUIT PEEL EXTRACT (HYLOCEREUS COSTARICENSIS) - Zahwa, Nabilla; Rosanti, Afi Sania; Dwiningrum, Riza; Daskar, Annajim (LPPM Universitas Dhyana Pura, 2025)
Solid soap is a body cleansing preparation commonly used to maintain skin health, especially for the purpose of perfuming, improving body odor. Some previous studies have developed solid soap formulations with red dragon fruit peel extract, but no studies have combined it with other natural ingredients that are humectant and antibacterial such as pure honey. The purpose of this study was to determine the concentration of formulations that provide the most effective stability results for solid bath soap preparations of dragon fruit peel extract combined with pure honey. The method used in this research is experimental, making simplisia of red dragon fruit skin then extracted with 70% ethanol solvent. Solid bath soap was formulated with different concentrations of pure honey and red dragon fruit peel extract in each formula. In this study, the results of formulation I did not meet the requirements on hardness and foam stability. Formulation II did not meet the requirements on pH, foam stability, and free fatty acids. Formulation III did not meet the requirements on pH, hardness, foam stability, and free fatty acids. Based on the hedonic test, formulation II was most liked by panelists on color, aroma, and shape. So it can be concluded that the characteristics of the three formulas differ based on the concentration levels of honey and extracts used and the most effective stability results are found in formulation I.